(untitled) (Research, Society and Development, 2021)
The general aim of the article is to identify the consequences of the government of Getúlio Vargas (1930-1945) for the state of Goiás. It was did a bibliographical research covering books, scientific articles, thesis and dissertations. And to describe the migration and production changes in Goiás were did documentary research, such as censuses from the Brazilian Institute of Geography and Statistics (IBGE), and the Official Report sent by the intervener Pedro Ludovico Teixeira to President Vargas (1930).The results found showed that the alignment of the Goiás policy with the federal government enabled significant changes for the state of Goiás, such as the construction of Goiânia and the National Agricultural Colony of Goiás (CANG). The effects of this partnership between state and federal policy between 1930-1945 can be seen in the increase of migration to the region and the growth of agricultural production. It is concluded that the period 1930-1945 was the beginning of the political process of insertion of Goiás into the national economy, because of the political arrangement at the time in the state and federal spheres.